2015
DOI: 10.1080/03601234.2015.1000166
|View full text |Cite
|
Sign up to set email alerts
|

Presence of PAHs in milk of industrial farms from Tizayuca, Hidalgo, Mexico

Abstract: The objective of this study was to determine the concentrations of polycyclic aromatic hydrocarbons (PAHs) in cow's milk from industrial farms that are located near an industrial park in Hidalgo, Mexico. It was found that the concentrations of PAHs in the raw milk of cattle from industrial farms have increased in recent years. Composite samples were collected between 2008 and 2010 and analysis carried out according to 8100 EPA procedures and analyzed by gas chromatography with FID detection. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
1
19
0
4
Order By: Relevance
“…This result was consistent with Naccari et al, who analyzed different types of milk using HPLC-MS [16]. The obtained results demonstrated that the presence of PAHs in raw milk was related to environmental pollution [8]. Furthermore, the formation of PAHs in milk can be affected by pasteurization and UHT treatments [16].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This result was consistent with Naccari et al, who analyzed different types of milk using HPLC-MS [16]. The obtained results demonstrated that the presence of PAHs in raw milk was related to environmental pollution [8]. Furthermore, the formation of PAHs in milk can be affected by pasteurization and UHT treatments [16].…”
Section: Resultssupporting
confidence: 89%
“…Sanagi et al also proved that many analyzed raw milk samples were contaminated with PAHs and Σ[PAHs] reached 33.3 µg/L [3]. The lack of detection of naphthalene in the analyzed samples was probably due to it being degraded or volatilized during the laboratory work [8]. In this study, we also found that the hydroxyl-metabolites from naphthalene and other derivatives of PAHs (not quantified) were found in most samples, which is presented in Table 4 and Figure 2.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…No existe un método oficial para la determinación de HAP en leche, existiendo dos tendencias en la identificación y cuantificación de los mismos: 1) por cromatografía gaseosa empleando detector de ionización de flama y espectrometría de masas (15,16) , 2) por cromatografía de líquidos de alta resolución con detector de fluorescencia (7,8,17) . Para obtener mejores resultados en la preparación de las muestras se han empleado diferentes procedimientos que incluyen saponificación, extracción líquido-líquido (LLE) y limpieza por cromatografía en columna o más recientemente, extracción en fase sólida (SPE) (18,19,20) .…”
Section: Introductionunclassified